求 [img=214x132]18034d5e4b29c11.png[/img] 的Z的反变换为 [img=217x132]18034d5e562a7d5.png[/img] 。
举一反三
- 求 [img=214x132]18039f02690cbe1.png[/img] 的Z的反变换为 [img=217x132]18039f0276a4597.png[/img] 。
- 求不定积分[img=115x46]17da65382f8e1b9.png[/img]; ( ) A: x - (5*log(x + 1))/4 - (3*log(x - 3)) B: (5*log(x + 1))/4 - (3*log(x - 3)) C: x - (5*log(x + 1))/4 - (3*log(x - 3))/4 D: (5*log(x + 1))/4 - (3*log(x - 3))/4
- 随机变量X服从均匀分布[img=246x104]1803bbdf7304c7f.png[/img]则E(X)=( ) A: 4 B: 5 C: 0.5 D: 1
- 设(X,Y)的联合密度为[img=246x61]17de89815546a18.png[/img],则EY=_____, E(XY)=_____. A: EY=4/5, E(XY)=7/5 B: EY=7/5, E(XY)=2/5 C: EY=3/5, E(XY)=1/2 D: EY=2/3, E(XY)=2/5
- 设随机变量X的密度函数为[img=452x125]1803b3b762030cd.png[/img]且E(X)=3/5,则常数a, b为 A: a=3/5, b=6/5 B: a=6/5, b=3/5 C: a=2/5, b=4/5 D: a=4/5, b=2/5